1α, 25‐dihydroxyvitamin D3 promotes osteogenic activity and downregulates proinflammatory cytokine expression in human periodontal ligament cells. (12th December 2014) - Nebel, D.; Svensson, D.; Arosenius, K.; Larsson, E.; Jönsson, D.; Nilsson, B.‐O.
<x xml:space="preserve">Abstract</x> Background and Objective The aim of this study was to assess the impact of 1α, 25‐dihydroxyvitamin D3 (vitamin D3) on osteogenic and inflammatory properties of human periodontal ligament (PDL) cells and investigate underlying mechanisms. Material and Methods Human PDL cells, obtained from four subjects, were stimulated with vitamin D3 for 4–48 h. The bone markers osteopontin and osteocalcin and proinflammatory cytokine/chemokine expression was determined by quantitative real‐time polymerase chain reaction and enzyme‐linked immunosorbent assay. Cytokine and chemokine expression was determined after stimulation with the inflammation promoter lipopolysaccharide (LPS) in the presence or absence of vitamin D3. Alkaline phosphatase activity was assessed using p‐nitrophenylphosphate substrate. Results Treatment with 30 ng/mL of vitamin D3, corresponding to an optimal plasma concentration of vitamin D, for 24 h had no effect on PDL cell number and morphology but increased PDL cell osteopontin and osteocalcin mRNA expression by about 70 and 40%, respectively, and, moreover, treatment with vitamin D3 for 48 h enhanced PDL cell alkaline phosphatase activity by about two times showing that vitamin D3 exerts pro‐osteogenic effects in human PDL cells. Stimulation with LPS (1 μg/mL) for 4 h increased PDL cell interleukin (IL)‐6 cytokine and chemokine ligand 1 (CXCL1) chemokine mRNA expression several fold. The LPS‐induced increase in IL‐6 and CXCL1 transcripts was attenuated by vitamin D3 (30 ng/mL). Treatment with vitamin D3 (3–300 ng/mL) for 24 h reduced the LPS‐evoked increase in PDL cell IL‐6 protein by about 50%. Vitamin D3 (30 ng/mL) had no effect on LPS‐induced IL‐1β and MCP‐1 mRNA expression. Conclusions Vitamin D3 promotes osteogenic differentiation but also downregulates inflammation promoter‐induced IL‐6 cytokine and CXCL1 chemokine expression in human PDL cells, suggesting that vitamin D3 both stimulates bone regeneration and antagonizes inflammation in human periodontal tissue.